ANTIBACTERIAL ACTIVITY OF ETHANOLIC EXTRACT OF JAVANESE TURMERIC RHIZOME ENTRAPPTED IN NANOPARTICLES: A NOVEL RULE OF CHITOSAN - Kumala, Shirly; Rahmat, Deni; Farida, Yunahara; Chandra, Benny (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to compare the antibacterial activity of 96% (v/v) ethanolic extract of Javanese turmeric rhizome (Curcuma xanthorrhiza Roxb.) and nanoparticles containing the extract against 4 pathogenic bacteria. Methods: The synthesis of chitosan nanoparticles used ionic gelation method. The nanoparticles were evaluated for particle size, zeta potential and morphology. Dilution method was performed to determine minimum inhibitory concentration (MIC). Results: The nanoparticles showed particle size of 53.25 nm, polydispersity index of 0.442 and zeta potential value of+31.5 mv. The antibacterial activity results based on the broth dilution method demonstrated that both the extract and the nanoparticles could inhibit the growth of Staphylococcus aureus, Escherichia coli, Salmonella thypi, and Bacillus subtilis in a concentration of 500 µg/ml. The MIC of the extract against Staphylococcus aureus and Bacillus subtilis were 400 µg/ml and against Escherichia coli and Salmonella thypi in a concentration of 500 µg/ml. In addition, the MIC of the nanoparticles against Staphylococcus aureus was 300 µg/ml while against Bacillus subtilis and Salmonella thypi 400 µg/ml and against Escherichia coli 500 µg/ml. Conclusion: The nanoparticles have a promising strategy to formulate the extracts in order to decrease the MIC against Staphylococcus aureus and Salmonella thypi.